PERANAN ORGANISASI DALAM MEMBENTUK KEPEMIMPINAN SISWA DI SEKOLAH MTS.S LAB. IKIP AL WASHLIYAH MEDAN - Khalisa, Nur (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2021)
Student Council at Mts.S LAB. IKIP AL Washliyah Medan is not only a forum for organization for students, but also a forum for interacting and collaborating between students with one another. Through the activities carried out by the Student Council, students can form their leadership character. This study aims to describe OSIS activities at Mts.S LAB. IKIP AL Washliyah Medan, to describe efforts to build student leadership characters at Mts.S LAB. IKIP AL Washliyah Medan, and describes the role of OSIS in shaping leadership character at Mts.S LAB. IKIP AL Washliyah Medan. This type of research is qualitative. The subjects of this study were the Student Council Deputy, Student Council Supervisor and OSIS Chair Mts.S LAB. IKIP AL Washliyah Medan as a key informant. The object of this research is the role of OSIS in shaping students' leadership character. Research data obtained through observation, interviews, and documentation. The results showed that: (1) Student Council in Mts.S LAB. IKIP AL Washliyah Medan has a work program and activities that have been determined at the beginning of the school year. These activities are in accordance with the functions and objectives of the Student Council. OSIS activities do not always go as planned, sometimes there are things that deviate and even these activities are not carried out. (2) One of the efforts to shape student leadership character is by carrying out student council activities, because in these activities all OSIS administrators and members are involved to make the event a success, and by becoming a committee will shape student leadership character. Student council activities are very influential in shaping student leadership character namely Student Leadership Basic Training activities. These activities teach students to be responsible leaders.